The Essence of using Steam Educational Technology in Primary Education (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article sheds light on the essence of using STEAM technology in the primary education process. It analyzes priority aspects such as interdisciplinary integration, the development of students' creative thinking, and the consolidation of knowledge through practical experiences. The study highlights the advantages of the STEAM method in developing problem-solving skills, increasing motivation, and organizing interactive lessons among elementary school students. Additionally, brief summaries and recommendations for implementing this approach in practice are provided.